Soviet Sexuality in the Mirror of Samizdat - Klumbys, Valdemaras (Genocidas ir rezistencija, 2023)
Transformations in sexuality which took place during the Soviet times were discussed only in the underground Catholic press and were viewed exclusively in a negative light. Often these transformations were seen as resulting from deliberate Soviet policies (especially atheization). However, the sexual discourses of underground press differed very little from conservative legal sexual discourses. This shows, on the one hand, that legal conservative texts not only expressed the family and sexuality policies of the framework of the time, but also reflected the opinion of the conservative part of Lithuanian society. On the other hand, this correlation shows the influence of state policies on Lithuanian society in non-political and non-legal realms. The similarities between underground press and the Stalinist sexual discourse are noteworthy, and it is possible to see the conservative and radicalising influence of the latter on the public’s attitude towards sexuality (including its Catholic part, then in the opposition). The manifestations of the influence of the Stalinist sexual discourse in the underground press of the ’70s and ’80s testify to the late influence of the sexual discourse, while the texts of the ’40s and ’50s show the influence of the Stalinist sexual discourse. The generation which reached adulthood in the ’50s was still reproducing it decades later. In the area of sexuality, most young people in principle could not find appeal in underground press as it was even further advanced in moralising than the Soviet press. Didacticism, which might have appealed to young people in the case of national and political self-awareness raising, was reduced to moralising in the moral sphere, and instead repelled the majority of youth by repeating the precepts of their elders and the postulates of the state propaganda. However, the ideal of chastity was able to have an impact on a part of society because it reflected society’s leaning towards conservatism and presented an alternative ideal to society, which was appealing due to its exceptionalism and individualism. The underground press could be broken down into a moderately conservative and an ultraconservative (ascetic) discourse on sexuality. The latter is distinguished from the former by a rigoristic and utopian approach to the body, pleasure, sexual relations, and chastity, which also has features of nationalistic Lithuanian messianism. Also noteworthy is the ascetic relationship of the discourse with the modernised position of the Church hierarchy, as decided by the Second Vatican Council. The relationship with modernisation in the texts analysed is distinctly negative: moral and ethical decline is constantly visible, and the present is compared to the idealised situation in inter-war Lithuanian society. This disappointment with the changes in society could be due to their inconsistency with the conservative values acquired during socialisation. This, together with the routinisation of modernist Soviet ideology, may have contributed to the intensification of religiosity in Lithuanian society in the ’70s and ’80s.